Attitude, Practice, and Awareness of Oral Hygiene Care among Nursing Professionals of a Tertiary Care Center of Malda in West Bengal: A Cross-sectional Study - Anjan Jana; Santanu Mukhopadhyay; Antarip Maji (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this study was to evaluate the knowledge, attitude, and practice of oral hygiene care among nursing professionals of a tertiary care center of Malda in West Bengal. Background: Oral cavity is the reflector of our general health. The relationship between oral health and systemic health is well established, but a lack of awareness and knowledge regarding dental hygiene restrains people from proper oral care. Most of the people including health workers do only brushing as their daily oral care process, ignoring the other important aspects of oral hygiene including regular tongue cleaning, use of interdental cleaning aids, change of toothbrush in a periodic manner, and regular dental checkups. Materials and Methods: A questionnaire-based descriptive cross-sectional study was carried out. After evaluating for the content validity and reliability, a self-structured questionnaire comprising ten questions about their oral hygiene was distributed among nursing professionals of Malda Medical College in a printed format after obtaining informed consent. Total 261 responses were gathered. Informed consent was obtained from each participant, and data were collected anonymously to maintain participants' confidentiality. The collected data were analyzed using the statistical software IBM SPSS for Windows, version 27.0. Results: Most of the participants use two times brushing as their regular dental care (77.4%) and use toothbrush and paste for the same (99.2%). Soft toothbrush is the most preferable choice (70.9%). Apart from brushing, other oral care methods are neglected, only 23.8% of participants use interdental cleaning aids, 79.3% use tongue cleaning, and only 8.8% have done regular dental checkups. Conclusion: The result of the present study depicts the limitation of knowledge and practice of oral hygiene care among nursing professionals of Malda Medical College. In spite of their health-care background, they have limited knowledge regarding regular oral hygiene care. Though most of them use two times brushing, but unaware about the importance of interdental cleaning and tongue cleaning habits.